3D bundled Ti-TiC reinforced aluminum-based composite material and preparation method thereof
By using 3D bundled Ti-TiC multi-stage configuration reinforcement in aluminum-based composite materials, combining non-uniform configuration and multi-stage enhancement, the problem that existing aluminum-based composite materials are difficult to have high strength and high toughness at the same time is solved, and the material is high tensile strength, good elongation and excellent wear resistance are achieved.
Patent Information
- Application Number
- CN202410415097.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-08
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-04-08
AI Technical Summary
It is difficult for existing aluminum-based composite materials to have high strength and high toughness at the same time, especially in the field of high-tech, the requirements for the comprehensive performance of materials are increasingly demanding.
A 3D bundled Ti-TiC multi-stage configuration reinforcement is adopted, and the reinforcement is titanium wire, dense TiC ceramic layer and TiC gradient composite layer in sequence along the radial center. Through the combination of non-uniform configuration and multi-stage enhancement, the overall performance of the material is improved.
It realizes the coordination and unity of strength and toughness of aluminum-based composite materials, has high tensile strength and good elongation, and at the same time improves the wear resistance of the material.
Smart Images

Figure CN118291892B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum-based composite materials, and relates to a 3D bundled Ti-TiC reinforced aluminum-based composite material and a preparation method thereof. Background Art
[0002] Aluminum-based composite materials are widely used in aerospace, military, automotive and other fields due to their excellent mechanical and physical properties such as high specific strength, specific stiffness, wear resistance, fatigue resistance, low thermal expansion, low density, high strength, good dimensional stability and thermal conductivity.
[0003] At present, the annual output of aluminum-based composite wear-resistant parts has reached more than 1,000 tons, and the reinforcing phases are mainly ceramic particles such as SiC, TiC, B4C, and Al2O3. Among them, the melting point of titanium carbide (TiC) ceramics is as high as 3140°C, and it has very high hardness. Its Mohs hardness is greater than 9. As a kind of ceramic, it has good chemical stability and is only soluble in nitric acid and aqua regia but not in other solvents. Since these ceramic phases have good wettability with aluminum liquid and high interface bonding strength with aluminum, the hardness, strength and wear resistance of composite wear-resistant parts can be greatly improved. However, as the volume fraction of the reinforcing phase increases, the strength of traditional particle-uniformly reinforced aluminum-based composite materials will continue to increase, while the toughness will decrease significantly.
[0004] However, with the continuous development of high-tech, the service environment of materials has become increasingly harsh, requiring materials to have high strength, high toughness and high wear resistance at the same time, that is, a good comprehensive performance match.
[0005] With the breakthrough in the basic theory of the transition from uniform distribution to controllable non-uniform distribution of the reinforcement phase, more and more studies have shown that the non-uniform configuration of the reinforcement phase has become a new strategy to effectively resolve the contradiction between strengthening and toughness. The non-uniform distribution of the reinforcement phase can achieve specific reinforcement in a specific direction of the material, and can also enrich the reinforcement phase in a specific area to avoid the uniform distribution of the reinforcement phase and reduce the intrinsic properties of the material on a large scale. At the same time, the mutual coordination of multi-level reinforcement and non-uniform configuration can improve the specific indicators of the material in a specific direction without reducing the overall performance of the material. Designing and preparing non-uniform composite configuration materials of ceramic particles and matrix is an effective solution to break through the mutual constraints between wear resistance and toughness of traditional particle-reinforced steel-based composite materials. Summary of the invention
[0006] One object of the present invention is to provide a 3D bundled Ti-TiC reinforced aluminum-based composite material, which solves the problem that the existing aluminum-based composite materials cannot have both high strength and high toughness.
[0007] Another object of the present invention is to provide a method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material.
[0008] The first technical solution adopted by the present invention is a 3D bundled Ti-TiC reinforced aluminum-based composite material, including an aluminum matrix, in which a 3D bundled Ti-TiC multi-level configuration reinforcement is distributed. The 3D bundled Ti-TiC multi-level configuration reinforcement is titanium wire, a dense TiC ceramic layer, and a TiC gradient composite layer in sequence from the radial center to the outside. The size of the TiC particles in the TiC gradient composite layer gradually increases outward along the radial direction.
[0009] Among them, the volume proportion of titanium wire in the 3D bundled Ti-TiC multi-level configuration reinforcement is not less than 20%, the volume proportion of the dense TiC ceramic layer is 10%~20%, and the rest is the TiC gradient composite layer.
[0010] The TiC gradient composite layer includes internal nano-scale TiC particles and external micron-scale TiC particles. The particle size of the nano-scale TiC particles is ≤50nm, the particle size of the external micron-scale TiC particles is 2μm~10μm, the particle size of the TiC particles in the dense TiC ceramic layer is ≤20nm, and the volume fraction of the TiC particles is ≥90%.
[0011] The volume fraction of TiC particles in the TiC gradient composite layer gradually decreases outward along the radial direction, from 85%~90% to 15%~20%.
[0012] The second technical solution adopted by the present invention is a method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material, comprising the following steps:
[0013] Step 1, preparing a 3D bundled Ti-TiC multi-level configuration reinforcement;
[0014] Step 2, copper-plating the surface of the aluminum powder, mixing the copper-plated aluminum powder with anhydrous ethanol in a ratio of 1-2:2-5, and then adding the 3D bundled Ti-TiC multi-level configuration reinforcement into the mixed solution in batches, stirring for 2-3 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum drying at 70-90° C. to obtain a mixed material;
[0015] Step 3, the mixed material obtained in step 2 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, heated to 750-800°C at 6-8°C / min and kept warm for 3h-5h, then cooled to 250-300°C at 3-5°C / min and cooled to room temperature with the furnace, with a full load of 20-30MPa, to obtain an aluminum-based composite material blank;
[0016] Step 4, performing aging heat treatment on the aluminum-based composite material blank, the aging treatment temperature is 200-300° C. After the aging heat treatment, a 3D bundled Ti-TiC multi-level configuration reinforced aluminum-based composite material is obtained.
[0017] Step 1 specifically includes the following steps:
[0018] Step 1.1, prepare some titanium wires with a titanium purity of 99.7-99.9%, pretreat the titanium wires to remove surface impurities and oxide layers;
[0019] Step 1.2, using ESP foam to make a lost foam, inserting titanium wire into the lost foam along the longitudinal direction to form an array arrangement, and the titanium wire is 10mm-30mm higher than the surface of the lost foam;
[0020] Step 1.3, brush refractory coating on the surface of the lost foam and dry it, then pack the lost foam into a box, fill the box with dry sand and compact it, cover the surface with plastic film, and connect the negative pressure system to form a lost foam casting system;
[0021] Step 1.4, selecting a ferrous metal with a carbon content greater than 0.4% and smelting it into a liquid state, and pouring it into the lost foam of step 1.3 at 1380-1420° C. to obtain a titanium wire-ferrous metal preform;
[0022] Step 1.5: The titanium wire-ferrous metal preform is kept at 1000-1150° C. for 1 h-5 h to obtain a 3D bundled Ti-TiC multi-level steel composite;
[0023] Step 1.6, immersing the 3D bundled Ti-TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heating the solution, deeply corroding the 3D bundled Ti-TiC multi-level structure steel composite, and then cleaning and drying to obtain a 3D bundled Ti-TiC multi-level structure reinforcement.
[0024] The diameter of the titanium wire in step 1.1 is 0.5mm-3mm. The titanium wire is pretreated, including first washing the titanium wire in 300mL / L of 10% NaOH solution to remove surface oil stains, rinsing with running water, then rinsing with 300mL / L of hydrochloric acid solution to remove the surface oxide film, rinsing with running water, and finally polishing the surface with sandpaper less than 800 mesh to roughen the surface, placing it in a beaker containing anhydrous ethanol, washing it with an ultrasonic vibrator, drying it, and putting it into a sealed bag for use.
[0025] In step 1.4, the ferrous metal is HT200, HT250, HT300, Q235 or Q345, which is poured into the lost foam of step 1.3 at 1380-1420°C for 40s-50s. Additional pouring is performed on the riser 1 minute after the pouring is completed.
[0026] In step 2, the surface of the aluminum powder is copper-plated, including pouring a chemical copper plating solution into the aluminum powder, and heating and stirring in a water bath at 50 to 80° C. When gas is generated in the solution, the water bath is removed, and the chemical copper plating solution is continued to be injected and stirred until the bubbles disappear. The above process is repeated until the blue color in the solution disappears completely, and the powder is filtered out and washed with H2SO4 and dried.
[0027] In step 2, the 3D bundled Ti-TiC multi-level configuration reinforcement is added to the mixed solution in batches, and the usage of the 3D bundled Ti-TiC multi-level configuration reinforcement is calculated based on the volume percentage of the 3D bundled Ti-TiC multi-level configuration reinforcement in the composite material of 10% to 40%.
[0028] The beneficial effects of the present invention are:
[0029] (1) The aluminum matrix of the present application is distributed with 3D bundled Ti-TiC multi-level configuration reinforcements, which combine the advantages of non-uniform configuration and multi-level reinforcement. From the radial center to the outside, there are titanium wires, dense TiC ceramic layers, and TiC gradient composite layers. Pure titanium has low hardness and good toughness, good ductility and toughness, can effectively avoid the initiation of cracks, and improve the overall performance of the composite material;
[0030] (2) The dense TiC ceramic layer can prevent the slip of dislocations and form dislocation accumulation, thereby deflecting the cracks and improving the overall strength of the composite material. In addition, the central titanium wire is surrounded by high-strength and high-hardness TiC ceramics, which is beneficial for its support and protection;
[0031] (3) The size of TiC particles in the TiC gradient composite layer gradually increases outward along the radial direction, which is beneficial to the transfer of load and improves the bonding performance between the dense TiC ceramic layer and the matrix. The titanium wire, dense TiC ceramic layer and TiC gradient composite layer synergistically realize the multi-level reinforcement of soft and hard materials and cross-scale particles, the gradient reinforcement of volume fraction gradient change and particle size gradient change, and the array arrangement of 3D bundled Ti-TiC multi-level configuration reinforcement body realizes non-uniform reinforcement, so that the 3D bundled Ti-TiC reinforced aluminum-based composite material has high strength, high toughness and excellent wear resistance at the same time;
[0032] (4) The present invention breaks the traditional concept of uniform dispersion of ceramic particles in the reinforcement phase of composite materials, and proposes a non-uniform configuration design idea that forms a 3D bundled Ti-TiC multi-level reinforcement with ceramic particle reinforcement phase, in which the reinforcement particles are enriched in the bundle area and the soft core material is wrapped in a high-strength and high-hardness ceramic layer to perform multi-level enhancement on the strength and toughness of the original material. The spatial bundle is mainly formed by multi-level coupling of the TiC reinforcement phase and the surface copper-plated matrix. Its macro interface presents a typical gradient characteristic, that is, the particle size and volume fraction of the TiC composite layer area change continuously, and the in-situ self-generated TiC and the matrix microphase interface are in good bonding state. The matching of the macro / micro interface can effectively improve the tensile strength of the composite material and relieve stress concentration, and can regulate the stress dissipation, load transfer and crack propagation behavior in the reinforcement body; at the same time, the core material with good ductility and toughness further blocks the initiation and propagation of cracks in the material, provides the material with reasonable toughness, and provides a new strategy for the good matching of strength and toughness of particle-reinforced aluminum-based composite materials, thereby achieving the coordinated unity of high strength, impact resistance and wear resistance of composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the internal structure of the 3D bundled Ti-TiC reinforced aluminum-based composite material of the present invention;
[0034] Figure 2 It is a schematic structural diagram of a 3D bundled Ti-TiC multi-level configuration reinforcement in the 3D bundled Ti-TiC reinforced aluminum-based composite material of the present invention;
[0035] Figure 3 It is a schematic diagram of the cross-sectional structure of a 3D bundled Ti-TiC multi-level configuration reinforcement in the 3D bundled Ti-TiC reinforced aluminum-based composite material of the present invention.
[0036] In the figure, 1. Nano-scale TiC particles, 2. Micron-scale TiC particles, 3. 3D bundled Ti-TiC multi-level configuration reinforcement, 4. Aluminum matrix, 5. Titanium wire, 6. Dense TiC ceramic layer, 7. TiC gradient composite layer. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] Example 1
[0039] A method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material comprises the following steps:
[0040] Step 1, preparing a 3D bundled Ti-TiC multi-level configuration reinforcement, specifically comprising the following steps:
[0041] Step 1.1, prepare some titanium wires with a titanium purity of 99.9% and a diameter of 0.5 mm. Cut them into small sections of 120 mm and pretreat the titanium wires, including first placing the titanium wires in a 300 mL / L 10% NaOH solution for cleaning for 10 min, removing surface oil stains and then rinsing with running water, then rinsing with a 300 mL / L hydrochloric acid solution to remove the surface oxide film, rinsing with running water, and finally polishing the surface with 400-mesh sandpaper to roughen the surface, placing it in a beaker containing anhydrous ethanol, cleaning it with an ultrasonic vibrator for 10 min, drying it, and putting it in a sealed bag for later use.
[0042] Step 1.2, using ESP foam to make a lost foam with a length, width and height of 100×100×100 mm, inserting the titanium wire into the lost foam along the longitudinal direction to form an array arrangement, and reserving 10 mm at both ends for positioning the titanium wire;
[0043] Step 1.3, apply refractory coating on the surface of the lost foam, and dry it in an oven at 70°C for 12 hours, repeat the refractory coating and drying operation once, then pack the lost foam into a box, fill the box with dry sand and vibrate it, cover the surface with plastic film and connect the negative pressure system to form a lost foam casting system;
[0044] Step 1.4, smelting HT200 gray cast iron into liquid, pouring it into the lost foam of step 1.3 at 1400°C, the pouring time is 40s, and pouring is performed on the riser 1 minute after the pouring is completed to obtain a titanium wire-ferrous metal preform.
[0045] Step 1.5: The titanium wire-ferrous metal preform is kept at 1000° C. for 1 hour to obtain a 3D bundle-shaped Ti-TiC multi-level steel composite;
[0046] Step 1.6, immerse the 3D bundled Ti-TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heat the solution to 50°C, pour out the upper waste liquid after soaking for 24 hours, repeat this process until the solution no longer turns green, filter it out from the solution with filter paper, then wash it 3 times, and dry it in a drying oven at 75°C for 2 hours to obtain the 3D bundled Ti-TiC multi-level structure reinforcement 3.
[0047] Step 2, copper plating the surface of the aluminum powder, including pouring chemical copper plating solution into the aluminum powder, heating and stirring in a 50°C water bath, when gas is generated in the solution, removing the water bath, continuing to inject chemical copper plating solution and stirring until the bubbles disappear, repeating the above process until the blue color in the solution completely disappears, filtering out the powder and washing and drying it with 99.9% H2SO4.
[0048] Step 3, according to the volume percentage of 10% of the 3D bundled Ti-TiC multi-level configuration reinforcement in the composite material, the required 3D bundled Ti-TiC multi-level configuration reinforcement is weighed, the surface copper-plated aluminum powder and anhydrous ethanol are mixed in a ratio of 1:2, and then the weighed 3D bundled Ti-TiC multi-level configuration reinforcement is added to the mixed solution in batches, stirred for 2 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum dried at 70° C. for 3 hours to obtain a mixed material;
[0049] Step 4, the mixed material obtained in step 3 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, the temperature is increased to 750°C at 6°C / min and kept at this temperature for 3h, then the temperature is decreased to 250°C at 3°C / min and cooled to room temperature with the furnace, the whole process load is 20MPa, and an aluminum-based composite material blank is obtained;
[0050] Step 5, performing aging heat treatment on the aluminum-based composite material blank at a temperature of 200° C., and obtaining a 3D bundled Ti-TiC multi-level configuration reinforced aluminum-based composite material after the aging heat treatment.
[0051] The prepared 3D bundled Ti-TiC reinforced aluminum matrix composite was observed for its internal structure. Figure 1 As shown, it includes an aluminum matrix 4, in which a 3D bundled Ti-TiC multi-level configuration reinforcement 3 is distributed. The entire reinforcement is a multi-layer structure, with the remaining titanium wire in the center, a pure TiC layer on the outside, and a TiC / Fe composite layer on the outside. This special structure helps to improve the strength of the material without reducing the toughness of the material.
[0052] Reference Figure 2 and Figure 3 The 3D bundled Ti-TiC multi-level configuration reinforcement 3 is composed of titanium wire 5, dense TiC ceramic layer 6, and TiC gradient composite layer 7 in sequence from the radial center to the outside. The size of TiC particles in the TiC gradient composite layer 7 gradually increases outward along the radial direction. The TiC gradient composite layer 7 includes nano-scale TiC particles 1 inside and micron-scale TiC particles 2 outside.
[0053] The physical properties of the 3D bundled Ti-TiC reinforced aluminum-based composite material prepared in Example 1 were tested. The micro-Vickers hardness of the dense TiC ceramic layer in the 3D bundled Ti-TiC multi-level reinforcement was 1980 HV 0.1 After adding 10% reinforcement by volume to aluminum, the tensile strength of the 3D bundled Ti-TiC reinforced aluminum-based composite material was measured to be 330MPa. Compared with the aluminum matrix, the tensile strength was increased by 22.2% and the elongation was decreased by 2%.
[0054] Example 2
[0055] A method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material comprises the following steps:
[0056] Step 1, preparing a 3D bundled Ti-TiC multi-level configuration reinforcement 3, specifically comprising the following steps:
[0057] Step 1.1, prepare some titanium wires with a titanium purity of 99.9% and a diameter of 1 mm, cut into small sections of 120 mm, and pretreat the titanium wires, including first placing the titanium wires in 300 mL / L of 10% NaOH solution for cleaning for 10 min to remove surface oil stains, rinsing with running water, then rinsing with 300 mL / L of hydrochloric acid solution to remove surface oxide film, rinsing with running water, and finally polishing the surface with 400-mesh sandpaper to roughen the surface, placing it in a beaker containing anhydrous ethanol, cleaning it with an ultrasonic vibrator for 10 min, drying it, and putting it in a sealed bag for use.
[0058] Step 1.2, using ESP foam to make a lost pattern with a length, width and height of 200×100×100 mm, inserting the titanium wire into the lost pattern along the longitudinal direction to form an array arrangement, and reserving 10 mm at both ends for positioning the titanium wire;
[0059] Step 1.3, apply refractory coating on the surface of the lost foam, and dry it in an oven at 70°C for 12 hours, repeat the refractory coating and drying operation once, then pack the lost foam into a box, fill the box with dry sand and vibrate it, cover the surface with plastic film and connect the negative pressure system to form a lost foam casting system;
[0060] Step 1.4, smelting HT250 gray cast iron into liquid, pouring it into the lost foam of step 1.3 at 1380°C, the pouring time is 40s, and pouring is performed on the riser 1 minute after the pouring is completed to obtain a titanium wire-ferrous metal preform.
[0061] Step 1.5: The titanium wire-ferrous metal preform is kept at 1050° C. for 1 hour to obtain a 3D bundle-shaped Ti-TiC multi-level steel composite;
[0062] Step 1.6, immerse the 3D bundled Ti-TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heat the solution to 50°C, pour out the upper waste liquid after soaking for 24 hours, repeat this process until the solution no longer turns green, filter it out from the solution with filter paper, then wash it 3 times, and dry it in a drying oven at 75°C for 2 hours to obtain a 3D bundled Ti-TiC multi-level structure reinforcement.
[0063] Step 2, copper plating the surface of the aluminum powder, including pouring chemical copper plating solution into the aluminum powder, heating and stirring in a 60°C water bath, when gas is generated in the solution, removing the water bath, continuing to inject chemical copper plating solution and stirring until the bubbles disappear, repeating the above process until the blue color in the solution completely disappears, filtering out the powder and washing and drying it with 99.9% H2SO4.
[0064] Step 3, according to the volume percentage of 20% of the 3D bundled Ti-TiC multi-level configuration reinforcement in the composite material, the required 3D bundled Ti-TiC multi-level configuration reinforcement is weighed, the surface copper-plated aluminum powder and anhydrous ethanol are mixed in a ratio of 2:5, and then the 3D bundled Ti-TiC multi-level configuration reinforcement is added to the mixed solution in batches, stirred for 3 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum dried at 90° C. for 5 hours to obtain a mixed material;
[0065] Step 4, the mixed material obtained in step 3 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, heated to 800°C at 8°C / min and kept at this temperature for 5 hours, then cooled to 300°C at 5°C / min and cooled to room temperature with the furnace, with a full load of 30MPa, to obtain an aluminum-based composite material blank;
[0066] Step 5, performing aging heat treatment on the aluminum-based composite material blank at a temperature of 300° C. After the aging heat treatment, a 3D bundled Ti-TiC multi-level configuration reinforced aluminum-based composite material is obtained.
[0067] The physical properties of the 3D bundled Ti-TiC reinforced aluminum-based composite material prepared in Example 2 were tested. The micro-Vickers hardness of the dense TiC ceramic layer in the 3D bundled Ti-TiC multi-level reinforcement was 2052 HV. 0.1 After adding 20% reinforcement by volume to aluminum, the tensile strength of the 3D bundled Ti-TiC reinforced aluminum-based composite material was measured to be 350MPa. Compared with the aluminum matrix, the tensile strength was increased by 29.6% and the elongation was decreased by 4%.
[0068] Example 3
[0069] A method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material comprises the following steps:
[0070] Step 1, preparing a 3D bundled Ti-TiC multi-level configuration reinforcement, specifically comprising the following steps:
[0071] Step 1.1, prepare some titanium wires, the diameter of the titanium wires is 2 mm, the titanium purity is 99.9%, and cut into small sections of 120 mm. Pretreat the titanium wires, including first placing the titanium wires in 300 mL / L of 10% NaOH solution for 10 minutes to remove surface oil stains, rinsing with running water, and then rinsing with 300 mL / L hydrochloric acid solution to remove the surface oxide film, rinsing with running water, and finally polishing the surface with 500-mesh sandpaper to roughen the surface, placing it in a beaker filled with anhydrous ethanol, cleaning it with an ultrasonic vibrator for 10 minutes, drying it, and putting it in a sealed bag for use.
[0072] Step 1.2, using ESP foam to make a lost foam with a length, width and height of 200×100×100 mm, inserting titanium wire into the lost foam along the longitudinal direction to form an array arrangement, with both ends of the titanium wire protruding 10 mm above the surface of the lost foam to locate the position of the titanium wire;
[0073] Step 1.3, apply refractory coating on the surface of the lost foam, and dry it in an oven at 70°C for 12 hours, repeat the refractory coating and drying operation once, then pack the lost foam into a box, fill the box with dry sand and vibrate it, cover the surface with plastic film and connect the negative pressure system to form a lost foam casting system;
[0074] Step 1.4, smelting HT300 gray cast iron into liquid, pouring it into the lost foam of step 1.3 at 1390°C, the pouring time is 45s, and pouring is performed on the riser 1 minute after the pouring is completed to obtain a titanium wire-ferrous metal preform.
[0075] Step 1.5: The titanium wire-ferrous metal preform is kept at 1100° C. for 1 hour to obtain a 3D bundle-shaped Ti-TiC multi-level steel composite;
[0076] Step 1.6, immerse the 3D bundled Ti-TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heat the solution to 50°C, pour out the upper waste liquid after soaking for 24 hours, repeat this process until the solution no longer turns green, filter it out from the solution with filter paper, then wash it 3 times, and dry it in a drying oven at 75°C for 2 hours to obtain a 3D bundled Ti-TiC multi-level structure reinforcement.
[0077] Step 2, copper plating the surface of the aluminum powder, including pouring chemical copper plating solution into the aluminum powder, heating and stirring in a 60°C water bath, when gas is generated in the solution, removing the water bath, continuing to inject chemical copper plating solution and stirring until the bubbles disappear, repeating the above process until the blue color in the solution completely disappears, filtering out the powder and washing and drying it with 99.9% H2SO4.
[0078] Step 3, according to the volume percentage of 3D bundled Ti-TiC multi-level configuration reinforcement in the composite material of 30%, the required 3D bundled Ti-TiC multi-level configuration reinforcement is weighed, the surface copper-plated aluminum powder and anhydrous ethanol are mixed in a ratio of 2:3, and then the 3D bundled Ti-TiC multi-level configuration reinforcement is added to the mixed solution in batches, stirred for 2.5 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum dried at 80° C. to obtain a mixed material;
[0079] Step 4, the mixed material obtained in step 3 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, heated to 800° C. at 7° C. / min and kept at that temperature for 4 h, then cooled to 250° C. at 4° C. / min and cooled to room temperature with the furnace, with a full load of 20 MPa, to obtain an aluminum-based composite material blank;
[0080] Step 5, performing aging heat treatment on the aluminum-based composite material blank at a temperature of 200° C., and obtaining a 3D bundled Ti-TiC multi-level configuration reinforced aluminum-based composite material after the aging heat treatment.
[0081] The physical properties of the 3D bundled Ti-TiC reinforced aluminum-based composite material prepared in Example 3 were tested. The micro-Vickers hardness of the dense TiC ceramic layer in the 3D bundled Ti-TiC multi-level reinforcement was 2105 HV 0.1 After adding 30% reinforcement by volume to aluminum, the tensile strength of the 3D bundled Ti-TiC reinforced aluminum-based composite material was measured to be 378MPa. Compared with the aluminum matrix, the tensile strength was increased by 45.3% and the elongation was decreased by 7%.
[0082] Example 4
[0083] A method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material comprises the following steps:
[0084] Step 1, preparing a 3D bundled Ti-TiC multi-level configuration reinforcement, specifically comprising the following steps:
[0085] Step 1.1, prepare some titanium wires, the diameter of the titanium wires is 3 mm, the titanium purity is 99.9%, and cut into small sections of 120 mm. Pretreat the titanium wires, including first placing the titanium wires in 300 mL / L of 10% NaOH solution to clean, remove surface oil stains, rinse with running water, then rinse with 300 mL / L hydrochloric acid solution to remove the surface oxide film, rinse with running water, and finally polish the surface with 400-mesh sandpaper to roughen the surface, place it in a beaker containing anhydrous ethanol, clean it with an ultrasonic vibrator for 10 minutes, dry it, and put it in a sealed bag for use.
[0086] Step 1.2, using ESP foam to make a lost foam with a length, width and height of 200×100×100 mm, inserting titanium wire into the lost foam along the longitudinal direction to form an array arrangement, with both ends of the titanium wire protruding 10 mm above the surface of the lost foam to locate the position of the titanium wire;
[0087] Step 1.3, apply refractory coating on the surface of the lost foam, and dry it in an oven at 70°C for 12 hours, repeat the refractory coating and drying operation once, then pack the lost foam into a box, fill the box with dry sand and vibrate it, cover the surface with plastic film and connect the negative pressure system to form a lost foam casting system;
[0088] Step 1.4, smelting Q235 into liquid, pouring it into the lost foam of step 1.3 at 1410°C, the pouring time is 45s, and one minute after the pouring is completed, additional pouring is performed on the riser to obtain a titanium wire-ferrous metal preform.
[0089] Step 1.5: The titanium wire-ferrous metal preform is kept at 1150° C. for 1 hour to obtain a 3D bundle-shaped Ti-TiC multi-level steel composite;
[0090] Step 1.6, immerse the 3D bundled Ti-TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heat the solution to 50°C, pour out the upper waste liquid after soaking for 24 hours, repeat this process until the solution no longer turns green, filter it out from the solution with filter paper, then wash it 3 times, and dry it in a drying oven at 75°C for 2 hours to obtain a 3D bundled Ti-TiC multi-level structure reinforcement.
[0091] Step 2, copper plating the surface of the aluminum powder, including pouring chemical copper plating solution into the aluminum powder, heating and stirring in a 50°C water bath, when gas is generated in the solution, removing the water bath, continuing to inject chemical copper plating solution and stirring until the bubbles disappear, repeating the above process until the blue color in the solution completely disappears, filtering out the powder and washing and drying it with 99.9% H2SO4.
[0092] Step 3, according to the volume percentage of 3D bundled Ti-TiC multi-level configuration reinforcement in the composite material of 40%, the required 3D bundled Ti-TiC multi-level configuration reinforcement is weighed, the surface copper-plated aluminum powder and anhydrous ethanol are mixed in a ratio of 1:5, and then the weighed 3D bundled Ti-TiC multi-level configuration reinforcement is added to the mixed solution in batches, stirred for 3 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum dried at 90° C. to obtain a mixed material;
[0093] Step 4, the mixed material obtained in step 3 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, the temperature is increased to 750°C at 6°C / min and kept at this temperature for 3 hours, then the temperature is decreased to 250°C at 5°C / min and cooled to room temperature with the furnace, the whole process load is 30MPa, and an aluminum-based composite material blank is obtained;
[0094] Step 5, performing aging heat treatment on the aluminum-based composite material blank at a temperature of 200° C., and obtaining a 3D bundled Ti-TiC multi-level configuration reinforced aluminum-based composite material after the aging heat treatment.
[0095] The physical properties of the 3D bundled Ti-TiC reinforced aluminum-based composite material prepared in Example 4 were tested. The micro-Vickers hardness of the dense TiC ceramic layer in the 3D bundled Ti-TiC multi-level configuration reinforcement was 2032 HV 0.1 After adding 40% reinforcement by volume to aluminum, the tensile strength of the 3D bundled Ti-TiC reinforced aluminum-based composite material was measured to be 366MPa. Compared with the aluminum alloy matrix, the tensile strength was increased by 40.7% and the elongation was decreased by 8%.
[0096] Example 5
[0097] A method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material comprises the following steps:
[0098] Step 1, preparing a 3D bundled Ti-TiC multi-level configuration reinforcement, specifically comprising the following steps:
[0099] Step 1.1, prepare some titanium wires, the diameter of the titanium wires is 3 mm, the titanium purity is 99.7%, and cut into small sections of 120 mm. Pretreat the titanium wires, including first placing the titanium wires in 300 mL / L of 10% NaOH solution for cleaning to remove surface oil stains, rinsing with running water, then rinsing with 300 mL / L of hydrochloric acid solution to remove the surface oxide film, rinsing with running water, and finally polishing the surface with 400-mesh sandpaper to roughen the surface, placing it in a beaker filled with anhydrous ethanol, cleaning it with an ultrasonic vibrator for 10 minutes, drying it, and putting it in a sealed bag for use.
[0100] Step 1.2, using ESP foam to make a lost pattern with a length, width and height of 200×100×100 mm, inserting the titanium wire into the lost pattern along the longitudinal direction to form an array arrangement, and reserving 10 mm at both ends for positioning the titanium wire;
[0101] Step 1.3, apply refractory coating on the surface of the lost foam, and dry it in an oven at 70°C for 12 hours, repeat the refractory coating and drying operation once, then pack the lost foam into a box, fill the box with dry sand and vibrate it, cover the surface with plastic film and connect the negative pressure system to form a lost foam casting system;
[0102] Step 1.4, smelting Q345 into liquid, pouring it into the lost foam of step 1.3 at 1420°C, the pouring time is 50s, and pouring at the riser 1 minute after the pouring is completed to obtain a titanium wire-ferrous metal preform.
[0103] Step 1.5: The titanium wire-ferrous metal preform is kept at 1150° C. for 5 hours to obtain a 3D bundle-shaped Ti-TiC multi-level steel composite;
[0104] Step 1.6, immerse the 3D bundled Ti-TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heat the solution to 50°C, pour out the upper waste liquid after soaking for 24 hours, repeat this process until the solution no longer turns green, filter it out from the solution with filter paper, then wash it 3 times, and dry it in a drying oven at 75°C for 2 hours to obtain a 3D bundled Ti-TiC multi-level structure reinforcement.
[0105] Step 2, copper plating the surface of the aluminum powder, including pouring chemical copper plating solution into the aluminum powder, heating and stirring in a water bath at 80°C, removing the water bath when gas is generated in the solution, continuing to inject chemical copper plating solution and stirring until the bubbles disappear, repeating the above process until the blue color in the solution completely disappears, filtering out the powder and washing and drying it with H2SO4 at a concentration of 99.9%.
[0106] Step 3, according to the volume percentage of 3D bundled Ti-TiC multi-level configuration reinforcement in the composite material of 40%, the required 3D bundled Ti-TiC multi-level configuration reinforcement is weighed, the surface copper-plated aluminum powder and anhydrous ethanol are mixed in a ratio of 1:3, and then the weighed 3D bundled Ti-TiC multi-level configuration reinforcement is added to the mixed solution in batches, stirred for 2 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum dried at 70° C. to obtain a mixed material;
[0107] Step 4, the mixed material obtained in step 3 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, the temperature is increased to 750°C at 8°C / min and kept at this temperature for 3 hours, then the temperature is decreased to 250°C at 5°C / min and cooled to room temperature with the furnace, the whole process load is 20MPa, and an aluminum-based composite material blank is obtained;
[0108] Step 5, performing aging heat treatment on the aluminum-based composite material blank at a temperature of 300° C. After the aging heat treatment, a 3D bundled Ti-TiC multi-level configuration reinforced aluminum-based composite material is obtained.
[0109] The physical properties of the 3D bundled Ti-TiC reinforced aluminum-based composite material prepared in Example 5 were tested. The micro-Vickers hardness of the dense TiC ceramic layer in the 3D bundled Ti-TiC multi-level reinforcement was 2089 HV. 0.1 After adding 40% reinforcement by volume to aluminum, the tensile strength of the 3D bundled Ti-TiC reinforced aluminum-based composite material was measured to be 375MPa. Compared with the aluminum alloy matrix, the tensile strength was increased by 42.2% and the elongation was decreased by 10%.
[0110] Comparative Example 1
[0111] A method for preparing a 3D bundled TiC reinforced aluminum-based composite material comprises the following steps:
[0112] Step 1, preparing a 3D bundled TiC multi-level configuration reinforcement, specifically comprising the following steps:
[0113] Step 1.1, prepare some titanium wires, the diameter of the titanium wires is 3 mm, the titanium purity is controlled at 99.9%, and cut into small sections of 120 mm. Pretreat the titanium wires, including first placing the titanium wires in 300 mL / L of 10% NaOH solution for cleaning to remove surface oil stains, rinsing with running water, and then rinsing with 300 mL / L of hydrochloric acid solution to remove the surface oxide film, rinsing with running water, and finally polishing the surface with 400-mesh sandpaper to roughen the surface, placing it in a beaker filled with anhydrous ethanol, cleaning it with an ultrasonic vibrator for 10 minutes, drying it, and putting it in a sealed bag for use.
[0114] Step 1.2, using ESP foam to make a lost pattern with a length, width and height of 200×100×100 mm, inserting the titanium wire into the lost pattern along the longitudinal direction to form an array arrangement, and reserving 10 mm at both ends for positioning the titanium wire;
[0115] Step 1.3, apply refractory coating on the surface of the lost foam, and dry it in an oven at 70°C for 18 hours, repeat the refractory coating and drying operation once, then pack the lost foam into a box, fill the box with dry sand and vibrate it, cover the surface with plastic film and connect the negative pressure system to form a lost foam casting system;
[0116] Step 1.4, smelting the gray cast iron into liquid, pouring it into the lost foam of step 1.3 at 1410°C, the pouring time is 40s, and pouring is performed on the riser 1 minute after the pouring is completed to obtain a titanium wire-ferrous metal preform.
[0117] Step 1.5: The titanium wire-ferrous metal preform is kept at 1200° C. for 12 hours, and the titanium wire in the preform and the carbon in the ferrous metal completely react to form TiC, thereby obtaining a 3D bundled TiC multi-level steel composite;
[0118] Step 1.6, immerse the 3D bundled TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heat the solution to 50°C, pour out the upper waste liquid after soaking for 24 hours, repeat this process until the solution no longer turns green, filter it out from the solution with filter paper, then wash it 3 times, and dry it in a drying oven at 75°C for 2 hours to obtain a 3D bundled TiC multi-level structure reinforcement.
[0119] Step 2, copper plating the surface of the aluminum powder, including pouring chemical copper plating solution into the aluminum powder, heating and stirring in a 70°C water bath, when gas is generated in the solution, removing the water bath, continuing to inject chemical copper plating solution and stirring until the bubbles disappear, repeating the above process until the blue color in the solution completely disappears, filtering out the powder and washing and drying it with 99.9% H2SO4.
[0120] Step 3, according to the volume percentage of 3D bundled TiC multi-level configuration reinforcement in the composite material of 40%, the required 3D bundled TiC multi-level configuration reinforcement is weighed, the surface copper-plated aluminum powder and anhydrous ethanol are mixed in a ratio of 2:5, and then the weighed 3D bundled TiC multi-level configuration reinforcement is added to the mixed solution in batches, stirred for 3 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum dried at 80° C. for 3 hours to obtain a mixed material;
[0121] Step 4, the mixed material obtained in step 3 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, heated to 780°C at 8°C / min and kept at this temperature for 3h, then cooled to 270°C at 4°C / min and cooled to room temperature with the furnace, with a full load of 25MPa, to obtain an aluminum-based composite material blank;
[0122] Step 5, performing aging heat treatment on the aluminum-based composite material blank at a temperature of 250° C., and obtaining a 3D bundled TiC multi-level configuration reinforced aluminum-based composite material after the aging heat treatment.
[0123] The physical properties of the 3D bundled TiC reinforced aluminum-based composite material prepared in Comparative Example 1 were tested. The micro-Vickers hardness of the dense TiC ceramic layer in the 3D bundled TiC multi-level reinforcement was 2109 HV. 0.1 After adding 40% reinforcement by volume to aluminum, the tensile strength of the 3D bundled TiC reinforced aluminum-based composite material was measured to be 375MPa. Compared with the aluminum matrix, the tensile strength was increased by 44.3% and the elongation was decreased by 25%.
[0124] The 3D bundled TiC multi-level configuration reinforced aluminum-based composite materials prepared in Examples 1-5 were observed. The volume proportion of titanium wire in the reinforcement was not less than 20%, the volume proportion of the dense TiC ceramic layer was 10%~20%, and the rest was the TiC gradient composite layer; the size of TiC particles in the TiC gradient composite layer 7 gradually increased outward in the radial direction, and the TiC gradient composite layer 7 included internal nanoscale TiC particles 1 and external micron-scale TiC particles 2. The particle size of the nanoscale TiC particles was ≤50nm, the particle size of the external micron-scale TiC particles was 2μm~10μm, the particle size of the TiC particles in the dense TiC ceramic layer was ≤20nm, and the volume fraction of TiC particles in the dense TiC ceramic layer was ≥90%, and the volume fraction of TiC particles in the TiC gradient composite layer in the composite material gradually decreased outward in the radial direction, from 85%~90% to 15%~20%.
[0125] The diameter of the reinforcement in the 3D bundled TiC multi-level configuration reinforced aluminum-based composite material prepared in Examples 1-4 was measured, and it was found that when the insulation time of the titanium wire and the ferrous metal preform was 1 h, as the insulation temperature increased from 1000°C to 1150°C, the diameter of the prepared 3D bundled Ti-TiC multi-level configuration reinforcement increased from 1.23 mm to 1.42 mm, and the proportion of the TiC gradient composite layer in the 3D bundled Ti-TiC multi-level configuration reinforcement increased from 40.62% to 49.57%.
[0126] From the comparative analysis of Examples 1, 2, 3, and 4, it can be seen that with the increase of the insulation temperature of the titanium wire-ferrous metal preform and the increase of the volume ratio of the 3D bundled Ti-TiC multi-level configuration reinforcement in the aluminum matrix, the strength of the prepared composite material first increases and then decreases. When the volume ratio of the 3D bundled Ti-TiC multi-level configuration reinforcement in the aluminum matrix is 30%, the overall strength of the composite material reaches the maximum value.
[0127] By comparing and analyzing Example 4, Example 5 and Comparative Example 1, as the holding time of the titanium wire-ferrous metal preform is prolonged, the proportion of the tough phase titanium wire in the reinforcement gradually decreases, and the overall strength of the composite material increases but the elongation decreases. It can be seen from Comparative Example 1 that when the holding time of the titanium wire-ferrous metal preform is 1200°C and the holding time is 12h, the titanium wire in the reinforcement reacts completely with the carbon, and the elongation of the composite material decreases significantly, which indicates that the presence of titanium wire in the 3D bundled Ti-TiC reinforcement has a significant effect on the toughness of the composite material, which is in line with the expected design.
Claims
1. A method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material, characterized in that: The following steps are involved: Step 1, preparing a 3D bundled Ti-TiC multi-level structure reinforcement (3); The step 1 specifically comprises the following steps: Step 1.1, prepare some titanium wires with a titanium purity of 99.7-99.9%, pretreat the titanium wires to remove surface impurities and oxide layers; Step 1.2, using ESP foam to make a lost foam, inserting titanium wire into the lost foam along the longitudinal direction to form an array arrangement, and the titanium wire is 10mm-30mm higher than the surface of the lost foam; Step 1.3, brush refractory coating on the surface of the lost foam and dry it, then pack the lost foam into a box, fill the box with dry sand and compact it, cover the surface with plastic film, and connect the negative pressure system to form a lost foam casting system; Step 1.4, selecting a ferrous metal with a carbon content greater than 0.4% and smelting it into a liquid state, and pouring it into the lost foam of step 1.3 at 1380-1420° C. to obtain a titanium wire-ferrous metal preform; In the step 1.4, the ferrous metal is HT200, HT250, HT300, Q235 or Q345, which is poured into the lost foam of step 1.3 at 1380-1420°C for 40s-50s, and the riser is filled with additional pouring 1 minute after the pouring is completed; Step 1.5: The titanium wire-ferrous metal preform is kept at 1000-1150° C. for 1-5 hours to obtain a 3D bundled Ti-TiC multi-level steel composite; Step 1.6, immersing the 3D bundled Ti-TiC multi-level structure steel composite in a concentrated hydrochloric acid solution, heating the solution, and deeply corroding the 3D bundled Ti-TiC multi-level structure steel composite until the solution no longer turns green, and then washing and drying to obtain a 3D bundled Ti-TiC multi-level structure reinforcement (3); Step 2, copper-plating the surface of the aluminum powder, mixing the copper-plated aluminum powder with anhydrous ethanol in a ratio of 1-2:2-5, and then adding the 3D bundled Ti-TiC multi-level configuration reinforcement into the mixed solution in batches, stirring for 2-3 hours until the aluminum powder is evenly covered on the reinforcement surface, and then vacuum drying at 70-90° C. to obtain a mixed material; Step 3, the mixed material obtained in step 2 is placed in a graphite mold, sealed and placed in a hot pressing sintering furnace, heated to 750-800°C at 6-8°C / min and kept warm for 3h-5h, then cooled to 250-300°C at 3-5°C / min and cooled to room temperature with the furnace, with a full load of 20-30MPa, to obtain an aluminum-based composite material blank; Step 4, performing aging heat treatment on the aluminum-based composite material blank, the aging treatment temperature is 200-300° C. After the aging heat treatment, a 3D bundled Ti-TiC multi-level configuration reinforced aluminum-based composite material is obtained.
2. The method for preparing the 3D bundled Ti-TiC reinforced aluminum-based composite material according to claim 1, characterized in that: The diameter of the titanium wire in step 1.1 is 0.5mm-3mm, and the titanium wire is pretreated, including first placing the titanium wire in 300mL / L of 10% NaOH solution for cleaning to remove surface oil stains, rinsing with running water, then rinsing with 300mL / L of hydrochloric acid solution to remove the surface oxide film, rinsing with running water, and finally polishing the surface with sandpaper less than 800 mesh to roughen the surface, placing it in a beaker containing anhydrous ethanol, cleaning it with an ultrasonic vibrator, drying it, and putting it into a sealed bag for use.
3. The method for preparing the 3D bundled Ti-TiC reinforced aluminum-based composite material according to claim 1, characterized in that: In the step 2, the surface of the aluminum powder is copper-plated, including pouring a chemical copper plating solution into the aluminum powder, and heating and stirring in a water bath at 50 to 80° C. When gas is generated in the solution, the water bath is removed, and the chemical copper plating solution is continuously injected and stirred until the bubbles disappear. The above process is repeated until the blue color in the solution disappears completely, and the powder is filtered out and washed with H2SO4 and dried.
4. The method for preparing the 3D bundled Ti-TiC reinforced aluminum-based composite material according to claim 1, characterized in that: In the step 2, the 3D bundled Ti-TiC multi-level configuration reinforcement is added to the mixed solution in batches, and the usage of the 3D bundled Ti-TiC multi-level configuration reinforcement is calculated based on the volume percentage of the 3D bundled Ti-TiC multi-level configuration reinforcement in the composite material of 10% to 40%.
5. A 3D bundled Ti-TiC reinforced aluminum-based composite material prepared by the method for preparing a 3D bundled Ti-TiC reinforced aluminum-based composite material according to any one of claims 1 to 4, characterized in that: The invention comprises an aluminum matrix (4), in which a 3D bundled Ti-TiC multi-level structure reinforcement body (3) is distributed. The 3D bundled Ti-TiC multi-level structure reinforcement body (3) is composed of titanium wire (5), a dense TiC ceramic layer (6), and a TiC gradient composite layer (7) in order from the center to the outside in the radial direction. The TiC particle size in the TiC gradient composite layer (7) gradually increases outward in the radial direction.
6. The 3D bundled Ti-TiC reinforced aluminum-based composite material according to claim 5, characterized in that: In the 3D bundled Ti-TiC multi-level configuration reinforcement (3), the volume proportion of the titanium wire (5) is not less than 20%, the volume proportion of the dense TiC ceramic layer (6) is 10% to 20%, and the rest is the TiC gradient composite layer (7).
7. The 3D bundled Ti-TiC reinforced aluminum-based composite material according to claim 6, characterized in that: The TiC gradient composite layer (7) comprises internal nano-scale TiC particles (1) and external micro-scale TiC particles (2); the particle size of the nano-scale TiC particles (1) is ≤50 nm, and the particle size of the micro-scale TiC particles (2) is 2 μm to 10 μm.
8. The 3D bundled Ti-TiC reinforced aluminum-based composite material according to claim 7, characterized in that: The volume fraction of TiC particles in the composite material in the TiC gradient composite layer (7) gradually decreases outward along the radial direction, from 85% to 90% to 15% to 20%.
Citation Information
Patent Citations
Preparation process of titanium carbide reinforced high manganese steel based composite material
CN101709438A
Nano TiC ceramic particle reinforced aluminum matrix composite and preparation method thereof
CN104532068A